Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy218
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Brain Development

Abstract: Adolescence is a time of significant social, emotional, and cognitive change. This chapter will review the literature on neurobiological changes that underlie these behaviors. We begin by operationalizing adolescence, then review how the conceptual frameworks and empirical studies in the field of developmental cognitive neuroscience have contributed to understanding this important developmental window and conclude by discussing the translational value of the basic science and implications for real‐world applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 388 publications
0
10
0
Order By: Relevance
“…The original program was designed to introduce the roles of, and the ways to deal with one’s cognition, and then proceed to deal with emotions. However, as adolescence is a phase marked with heightened emotionality [ 46 ] and the interdependent nature of the Japanese self-construct would likely make them more susceptible to others’ emotions rather than their own cognition [ 27 ], we modified the lesson order to first introduce and deal with emotions, then proceed to cognition. The modification process was carefully discussed with relevant professionals, practitioners, as well as the original program developers.…”
Section: Methodsmentioning
confidence: 99%
“…The original program was designed to introduce the roles of, and the ways to deal with one’s cognition, and then proceed to deal with emotions. However, as adolescence is a phase marked with heightened emotionality [ 46 ] and the interdependent nature of the Japanese self-construct would likely make them more susceptible to others’ emotions rather than their own cognition [ 27 ], we modified the lesson order to first introduce and deal with emotions, then proceed to cognition. The modification process was carefully discussed with relevant professionals, practitioners, as well as the original program developers.…”
Section: Methodsmentioning
confidence: 99%
“…Another key aspect of development reflected herein is the explicit emphasis on adolescence, a developmental period characterized by dynamic neural and physiological changes that precipitate, maintain, and that are influenced by commensurate changes in peer and family interactions (see excellent review of Galván & Tottenham, 2016). Andershed et al (this issue), for example, employed developmentally indicated expansion into alcohol, nicotine, and substance use domains; that youth psychopathic traits showed predictive utility for this crucial constellation of adolescent behaviors suggests that early detection intervention of psychopathic traits may reduce the adolescent alcohol/substance problems and/or make them more amenable to interventions.…”
Section: Studies Of This Special Sectionmentioning
confidence: 99%
“…One of the most popular risk‐taking behavior frameworks to recently evolve, Steinberg’s (2010) Dual‐Systems Model, posits that increases in risk‐taking behavior during adolescence are a result of heightened sensitivity to the social context and associated rewards (i.e., peer acceptance) in conjunction with slower developing neuro‐cognitive processes linked to self‐regulation. Developmental timing differences between higher order neuro‐cognitive processes (e.g., decision‐making) and neural reward pathways (e.g., dopaminergic system) in adolescence have been confirmed by multiple neuroscience studies (Casey et al., 2008; Chein et al., 2011; Galván & Tottenham, 2016). Beyond its focus on normative adolescent development, the Dual‐Systems Model can also be used to inform the increased vulnerability to substance use obese adolescents may encounter.…”
Section: Pathways and Processes Underlying Obesity To Substance Use I...mentioning
confidence: 87%
“…Recent methodological advances in developmental affective neuroscience indicate that a combination of significant biological, neuro‐cognitive, and socio‐emotional changes explain the increase in risk‐taking observed from adolescence through the transition to young adulthood (Casey, Getz, & Galvan, 2008; Chein, Albert, O’Brien, Uckert, & Steinberg, 2011; Galván & Tottenham, 2016). At the core of these changes is the adolescent peer context.…”
Section: Pathways and Processes Underlying Obesity To Substance Use I...mentioning
confidence: 99%